Family‐building and parenting considerations for people with cystic fibrosis. (18th August 2021) - Kazmerski, Traci M.; West, Natalie E.; Jain, Raksha; Uluer, Ahmet; Georgiopoulos, Anna M.; Aitken, Moira L.; Taylor‐Cousar, Jennifer L.
Abstract: As people with cystic fibrosis (CF) live longer and healthier lives, increasing numbers are considering the full range of reproductive options for their futures, including parenthood, pregnancy, or pregnancy prevention. As the face of CF changes, the CF care model must adapt to meet the reproductive health needs of both parents and nonparents with CF. This article summarizes the reproductive goals and family‐building concerns faced by people with CF, including fertility, pregnancy, and alternative paths to parenthood, the impact of parenthood on mental and physical health, and important future research.